USE OF SOCIAL MEDIA APPLICATIONS BY LIS PROFESSIONALS IN HIGHER EDUCATION INSTITUTIONS IN KARNATAKA: A STUDY - Kishora H V (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study explores the usage patterns of social media applications by library and information science (LIS) professionals in higher education institutions in Karnataka, India. The results obtained through a survey of 424 library professionals indicate a widespread adoption of social media applications among library professionals, with 96.7% of respondents affirming their usage. The study delves further into the specific social media tools employed by library professionals, revealing that Facebook, Instagram, WhatsApp, and LinkedIn are the most frequently used platforms. Additionally, academic-related social media tools like ResearchGate and LinkedIn are notably popular, while others such as RefWorks and Zotero see limited use. Library professionals predominantly utilize social media for communication with users, sharing information about library resources, and providing services such as current awareness services and selective dissemination of information. Furthermore, the research unveils the role of social media in engaging the research community, with platforms like ResearchGate and Academia.edu being prominent choices. These findings have implications for designing effective training programs, optimizing social media applications, and formulating policies to harness the potential of social media for enriching library services and fostering professional development among LIS professionals in higher education institutions.